The Influence of the Discovery Learning Learning Model on Critical Thinking Abilities and Student Learning Outcomes in Buffer Solution Material - Sri Ayuningsih; Laili Nailul Muna (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to determine the effect of the discovery learning model on critical thinking skills and student learning outcomes in buffer solution material for class XI MIPA at SMA Negeri 1 Kejobong. This research uses a quasi-experimental type of research which was carried out in March – April 2023. The sampling technique used was cluster random sampling. The population consists of three classes XI MIPA, totaling 101 students. The samples used were class XI MIPA 1 as an experimental class with a total of 31 students and class XI MIPA 2 as a control class with a total of 34 students. The instruments used were critical thinking ability questionnaires and multiple choice questions. The results of this research indicate that the use of the discovery learning model in learning buffer solution material can improve critical thinking skills and student learning outcomes. This is evident from the average critical thinking ability score of experimental class students of 58.32 while the control class is 55.29. The average value of student learning outcomes for the experimental class was 84.77 and the control class was 79.53. The conclusion from the results of this research is that there is an influence of the discovery learning model on critical thinking skills and student learning outcomes in buffer solution material for class XI MIPA at SMA Negeri 1 Kejobong.